З історії повернення фотодокументів ЦДКФФА України ім. Г. С С. Пшеничного, вивезених у роки Другої світової війни - Ємельянова, Т. (Архіви України, 2009)
In a historical succession is recreated the process of searching and returning documentary photographs of the Central State Film, Photo and Sound Archive named after G. S. Pshenichny, taken out in the years of World War II. There are published documentary photographs from the last receipt, dedicated to defence capability of the USSR.